Clinicopathological evaluation of acute appendicitis and the role of ultrasound in diagnosis: a prospective study - Mathew, Tony; Ammanagi, Amit Shivshankar (International Surgery Journal, 2019)
Background: Acute appendicitis is the most common acute surgical condition of the abdomen. Delay in treatment of acute appendicitis causes lot of complication. Study was done with the objective to study the clinical and pathological presentations of acute appendicitis, to evaluate the role of ultrasound in early diagnosis of acute appendicitis and to reduce negative appendicectomy in patients. Methods: This is a prospective study done on 100 patients with acute right lower abdominal pain clinically presumed to be of appendicular origin. A thorough history, clinical examination and ultrasound scan, was done for all cases. All ultrasound positive cases were subjected to surgery and some negative cases were also taken for surgery based on clinical suspicion. The ultrasound diagnosis was compared with clinical findings, operative findings and histopathological examination reports. Results: The overall accuracy of clinical diagnosis (Alvarado scoring system) with histopathology findings was 72%. The overall sensitivity and specificity was 70.3% and 81.3% respectively and positive predictive value of was 95.2% whereas the negative predictive value was 34.2%. The overall accuracy of ultrasound with histopathology report was 93%, with a sensitivity of 96.4%, specificity of 75%, and a positive predictive value of 95% and a negative predictive value of 80%. Negative appendicectomy rate was 8.82% in females and 3.63% in males. Conclusions: The Alvarado scoring system combined with ultrasound can therefore be used as a cheap and inexpensive way of confirming acute appendicitis thus reducing negative appendicectomy rate.